2000
DOI: 10.1042/bj3500181
|View full text |Cite
|
Sign up to set email alerts
|

Catabolism of aggrecan, decorin and biglycan in tendon

Abstract: We have examined the catabolism of the proteoglycans aggrecan, decorin and biglycan in fresh tendon samples and in explant cultures of tissue from the tensional and compressed regions of young and mature bovine tendons. A panel of well-characterized antibodies that recognize glycosaminoglycan or protein (linear or neoepitope) sequences was used to detect proteoglycans and proteoglycan degradation products that were both retained within the tissue and released into the culture medium. In addition, a reverse-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 43 publications
7
68
0
2
Order By: Relevance
“…Several members of this family have been demonstrated to have aggrecanase activity, including ADAMTS-1, ADAMTS-4, ADAMTS-5, ADAMTS-8, ADAMTS-9 and ADAMTS-15 (Porter et al, 2005). Within tendon, mRNA expression for both ADAMTS-4 and ADAMTS-5 has been detected (Rees et al, 2000;Tsuzaki et al, 2003), however it remains to be established as to whether other aggrecanases are also present in the tissue. Significantly, within explant cultures of tendon, considerable degradation of aggrecan occurs, and aggrecanase activity is present in the absence of catabolic stimulation, suggesting that the aggrecanases have a prominent role in constitutive catabolism of tendon aggrecan (Rees et al, 2005(Rees et al, , 2000.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Several members of this family have been demonstrated to have aggrecanase activity, including ADAMTS-1, ADAMTS-4, ADAMTS-5, ADAMTS-8, ADAMTS-9 and ADAMTS-15 (Porter et al, 2005). Within tendon, mRNA expression for both ADAMTS-4 and ADAMTS-5 has been detected (Rees et al, 2000;Tsuzaki et al, 2003), however it remains to be established as to whether other aggrecanases are also present in the tissue. Significantly, within explant cultures of tendon, considerable degradation of aggrecan occurs, and aggrecanase activity is present in the absence of catabolic stimulation, suggesting that the aggrecanases have a prominent role in constitutive catabolism of tendon aggrecan (Rees et al, 2005(Rees et al, , 2000.…”
Section: Introductionmentioning
confidence: 94%
“…In this regard, it has been proposed that the increased aggrecan mRNA expression and glycosaminoglycan levels that occur in painful tendinopathy may reflect an altered mechanical environment at the site of the lesion, resulting in a fibrocartilaginous expression pattern (Corps et al, 2006). We and others have demonstrated that aggrecan degradation in tendon is mediated principally via proteolysis of specific Glu-Xaa bonds, by 'aggrecanases' which are members of the ADAMTS (A Disintegrin And Metalloproteinase with Thrombospondin motifs) family of proteinases (Rees et al, 2000;Samiric et al, 2004b). Several members of this family have been demonstrated to have aggrecanase activity, including ADAMTS-1, ADAMTS-4, ADAMTS-5, ADAMTS-8, ADAMTS-9 and ADAMTS-15 (Porter et al, 2005).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Tenocytes are embedded in an extensive three-dimensional network of extracellular matrix components consisting predominantly of collagen type I fibrils (>95% of tendon collagen), other types of collagen (type III and type V), proteoglycans, elastin and fibronectin (Bernard-Beaubois et al 1997;Kannus 2000;Rees et al 2000). These tendon-specific matrix components give tendon its resilience and biomechanical stability.…”
Section: Introductionmentioning
confidence: 99%
“…Reverse transcription-polymerase chain reactions (RT-PCR) were performed using an RNA PCR kit (PerkinElmer) as described previously [37] using oligonucleotide primers specific to cyclooxygenase cDNA sequences (see Table 1). Following an initial denaturation step of 1 min at 95°C, amplification consisted of 30-45 cycles of 1 min at 95°C, 45 s at the individual annealing temperature of the primers (Table 1), 30 s at 72°C, followed by a final extension step of 5 min at 72°C.…”
Section: Rna Extraction and Pcr Analysismentioning
confidence: 99%